2019
DOI: 10.1109/access.2019.2892624
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Classification and Crowd Source Sensing; A Lexicon Based Approach

Abstract: In today's world, social media provides a valuable platform for conveying expressions, thoughts, point-of-views, and communication between people, from diverse walks of life. There are currently approximately 2.62 billion active users' social networks, and this is expected to exceed 3 billion users by 2021. Social networks used to share ideas and information, allowing interaction across communities, organizations, and so forth. Recent studies have found that the typical individual uses these platforms between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Vasileios Lampos et al [5] have used an approach of analyzing the t witter data to monitor the diffusion of pandemic in people. Rashid Kamal et al [6] proposed a crowd source sensing technique using twitter data and word model which can classify the emotions and proved to be more efficient when analysis is done based on location. In many twitter dataset available, location fro m which tweet is sent is not mentioned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vasileios Lampos et al [5] have used an approach of analyzing the t witter data to monitor the diffusion of pandemic in people. Rashid Kamal et al [6] proposed a crowd source sensing technique using twitter data and word model which can classify the emotions and proved to be more efficient when analysis is done based on location. In many twitter dataset available, location fro m which tweet is sent is not mentioned.…”
Section: Literature Reviewmentioning
confidence: 99%
“…-Ex3: "avlgee kannada baralla avl enu kannada kalstale" -Translation: "She doesn't know Kannada how she can teach Kannada" -Google Translation: "What is Kannada?" To address the above limitations, few researchers are trying to use the lexicon-based approach for emotion prediction [14]. Here, the lexicon-based approach does not require any training data and these are computationally not expensive in comparison with ML and DL.…”
Section: Figure 1 Different Approaches For Emotion Predictionmentioning
confidence: 99%
“…The research was conducted on 18,659 advertisement tweets by three major cell phone companies selling their phones in India, the results of which revealed that Xiaomi appears, in every aspect, to be the winner of all the three brand names -Xiaomi, Honor, and OnePlus, irrespective of the scope of SM. In the same year, a study by Fernández-Gavilanes, Juncal-Martínez, García-Méndez, Costa-Montenegro, & González-Castaño proposed the combination of the position prediction approach with an unmonitored SA strategy to assess, automatically, the presence in various countries of social network users during an event of global impact [15]. A study was done to examine users' or potential consumer preferences to evaluate users' emotional responses to different types of posts (images or video) distributed through SM channels.…”
Section: Data Presentationmentioning
confidence: 99%